Understanding beliefs, preferences and actions amongst potential body donors. Issue 2 (11th July 2022) - Smith, Claire F.; Munro, Ross; Davies, D. Ceri; Wilkinson, Tracey; Shaw, Hannah; Claridge, Kim; Llewellyn, Sarah; Mc Ateer, Philomena; Ward, Siobhan; Farsides, Tom
Abstract: Body donation is a prosocial act providing a unique learning experience to students, ultimately impacting on patient care and science. With an increasing number of training professionals, there is an increasing need for body donors, yet little is understood about donors' beliefs and preferences. A four‐center study aimed to understand donors' perceptions, 843 responses highlighted a significant relationship between completing a body donor consent form and being both an organ donor and having ever donated blood ( p  < 0.01). In exploring donor intentions, 69% had been considering donation for fewer than five years, 40% knew another body donor, and 27% had a family member or friend currently registered. Of those who had requested donor information packs, 97% had completed body donation consent forms. Of these, 92% had not selected any time restriction for their donation and 96% had consented to images being taken. Almost all (98%) were aware that their donation might not be accepted. Donors' motives highlighted a wish to: improve education, improve health care, advance science, and contribute to the greater good. A bimodal response was observed with body donation being used to save relatives money and inconvenience. Donors felt comfortable with their bodies being used by medical, dental, and allied health professionals; however, donors were less comfortable with their bodies being used by other groups. Only 57% were comfortable with artists, beauticians and yoga teachers using their remains. Understanding donors' motivations and decision‐making process is vital to ensure resources for future and to meet any changing requirements of both donors and those studying them.